Adaptasi Beberapa Varietas Kedelai (Glycine max (L.) Merril) Berdaya Hasil Tinggi Pada Lahan Kering Di Prafi Mulya Sp-1 Manokwari : Pengamatan Terhadap Komponen Pertumbuhan - Benny M. D. Layala; Dwi Wasgito Purnomo; Yohanis Amos Mustamu (Agrotek, 2015)
The purpose of this study was to determine the adaptation of some high yield soybean varieties at dryland area in Prafi Mulya SP-1, Manokwari district. The randomized block design used in this study which consisted of 9 varieaties as the treatment, such as Grobogan, Mutiara, Anjasmoro, Detam-2, Burangrang, Agromulyo, Pangrango,Tanggamus and Local Prafi. The result showed that there was a significant effect ofsoybean varieties to the plant height and branch number.